2008
DOI: 10.1677/jme-08-0062
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 and MafA regulate islet-specific glucose-6-phosphatase catalytic subunit-related protein gene expression

Abstract: Islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP/G6PC2) is a major autoantigen in both mouse and human type 1 diabetes. IGRP is selectively expressed in islet b cells and polymorphisms in the IGRP gene have recently been associated with variations in fasting blood glucose levels and cardiovascular-associated mortality in humans. Chromatin immunoprecipitation (ChIP) assays have shown that the IGRP promoter binds the islet-enriched transcription factors Pax-6 and BETA2. We show here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…Hamster insulinoma tumor (HIT), βTC-3 and Min6 cells were cultured and transfected with various G6PC2-luciferase fusion genes in the pGL3 MOD vector (2 µg) and an expression vector encoding Renilla luciferase (0.5 µg) using lipofectamine as previously described [3, 25]. Following transfection, cells were incubated for 18–20 hr in serum-containing medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamster insulinoma tumor (HIT), βTC-3 and Min6 cells were cultured and transfected with various G6PC2-luciferase fusion genes in the pGL3 MOD vector (2 µg) and an expression vector encoding Renilla luciferase (0.5 µg) using lipofectamine as previously described [3, 25]. Following transfection, cells were incubated for 18–20 hr in serum-containing medium.…”
Section: Methodsmentioning
confidence: 99%
“…Following transfection, cells were incubated for 18–20 hr in serum-containing medium. The cells were then harvested and firefly and Renilla luciferase activity were assayed as previously described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Our functional analysis of the rs573225 variant in ␤-cell lines found that the G allele was able to bind Foxa2 factor more efficiently than the A allele and was associated with a higher G6PC2 promoter activity. Previous studies have found that several mutated transcription factor sites located in G6PC2 promoter could modify its expression (6,17). Studies reviewed in Martin et al (6) support a positive role for Foxa2 in G6PC2 expression and a negative impact on insulin secretion in vitro (18 -20).…”
Section: Foxa2 Binding Site Of the G6pc2 Promotermentioning
confidence: 96%
“…Previous studies have found that several mutated transcription factor sites located in G6PC2 promoter could modify its expression (6,17). Studies reviewed in Martin et al (6) support a positive role for Foxa2 in G6PC2 expression and a negative impact on insulin secretion in vitro (18 -20). G6PC2 appears to negatively affect stimulus-secretion coupling (3).…”
Section: Foxa2 Binding Site Of the G6pc2 Promotermentioning
confidence: 96%
See 1 more Smart Citation